The effect of Ownership Structure on accounting conservatism for companies listed on the Iraq Stock Exchange - Tariq Hatim Rahi; Dhrgham Ibrahim Kadhim AL.Shukri; Rami meteab ali Alreshawee (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
This study examined the relationship between ownership structure and accounting conservatism in 30 companies listed on the Iraqi Stock Exchange over 5 years from 2015 to 2019. The main hypothesis of this study is to examine the existence of a significant relationship between ownership structure and accounting conservatism. To examine the ownership structure, the ownership of the largest shareholder, active and inactive institutional shareholders, real shareholders, and finally, the members of the board of directors have been considered. The Givoly & Hayn model was used to test conservatism. There is a significant relationship between the largest shareholder, percentage of active institutional shareholders, and ownership of board members, and no significant relationship was found between inactive institutional shareholders, real shareholders and accounting conservatism.